Visión empresarial a través del espíritu emprendedor de los estudiantes que cursan la unidad de aprendizaje del ámbito empresarial en la UANL, FACPYA (Business vision through its entrepreneurial spirit of the students who attend the Learning Unit of the business sector in the UANL, FACPYA) - Carrera Sánchez, María Margarita; Partida Puente, Abel; Villarreal Villarreal, Luis Alberto (Imprenta Universitaria de la Universidad Autónoma de Nuevo León, 2016)
Abstract: This research aims to recognize the characteristics that form the entrepreneurship and how these essential characteristics contribute to the entrepreneurial vision of university students of the Facultad de Contaduría Pública y Administración of UANL in the development of new businesses, identifying the attributes that foster entrepreneurship, such as: the ability to face risk situations, the tools, the knowledge, the values, the abilities, the entrepreneurial profile and to demonstrate how those attributes affect the development of college students in the creation of new businesses. The collected data was obtained from a questionnaire, validated and reliable; it was examined with the statistical package SPSS-V18. Using multiple linear regression, a goodness-of-fit test of the normal distribution, heterogeneity and linearity was performed. The results show the significance of the variable (X4), the values and personality traits (X6), with a positive impact on college students in generating new business, while the study variables (X1) skills, (X2) tools, (X3) knowledge, (X5) talents, are not significant. The study was delimited to students of the Universidad Autónoma de Nuevo Leon, the scientific method was used through a quantitative and qualitative study based on a simple linear regression.